Spatial patterns and links between microbial community composition and function in cyanobacterial mats - Al-Najjar, Mohammad A. A.; Ramette, Alban; Kühl, Michael; Hamza, Waleed; Klatt, Judith M.; Polerecky, Lubos (Frontiers in Microbiology, 2014)
We imaged reflectance and variable fluorescence in 25 cyanobacterial mats from 4 distant sites around the globe to assess, at different scales of resolution, spatial variabilities in the physiological parameters characterizing their photosynthetic capacity, including the absorptivity by chlorophyll a (A_chl), maximum quantum yield of photosynthesis (Y_max) and light acclimation irradiance (I_k). Generally, these parameters significantly varied within individual mats on a sub-millimeter scale, with about 2-fold higher variability in the vertical than in the horizontal direction. The average vertical profiles of Y_max and I_k decreased with depth in the mat, while A_chl exhibited a sub-surface maximum. The within-mat variability was comparable to, but often larger than, the between-sites variability, whereas the within-site variabilities (i.e., between samples from the same site) were generally lowest. When compared based on averaged values of their photosynthetic parameters, mats clustered according to their site of origin. Similar clustering was found when the community composition of the mats' cyanobacterial layers were compared by automated ribosomal intergenic spacer analysis, indicating a significant link between the microbial community composition and function. Although this link is likely the result of community adaptation to the prevailing site-specific environmental conditions, our present data is insufficient to identify the main factors determining these patterns. Nevertheless, this study demonstrates that the spatial variability in the photosynthetic capacity and light acclimation of benthic phototrophic microbial communities is at least as large on a sub-millimeter scale as it is on a global scale, and suggests that this pattern of variability scaling is similar for the microbial community composition.